THE SYSTEM OF IMPOSING FINES FOR LATE PAYMENT OF ELECTRICITY BILLS AT PT PLN ACCORDING TO SHARIA ECONOMIC LAW - Tiara Maya Santhia; Hajarul Akbar (JURISTA: Jurnal Hukum dan Keadilan, 2025)
This study was prompted by the disproportionate enforcement of the penalty system for late electricity bill payments by PT PLN, a state-owned electricity provider in Indonesia, particularly in low-income neighbourhoods. The current penalty system is mainly uniform. It disregards the socio-economic conditions of customers and is therefore considered inconsistent with the ideals of justice articulated in Islamic economics. This study aims to analyse the framework for imposing fines on late electricity bill payments through the lens of Islamic economic law and assess its alignment with the principles of maqashid syariah, including justice (al-‘adl), public interest (al-maslahah), and the prohibition of usury (riba). The study employs a descriptive qualitative methodology, incorporating a literature review and data collection through interviews, observations, and documentation of PLN policies. The findings indicate that PLN's penalty policy lacks transparency and has not been sufficiently explained to customers. The monies accrued from penalties are not designated for social objectives, contrary to the recommendations of Islamic economic fatwas. This study advocates for the reformulation of penalty policies to enhance fairness and proportionality, including the provision of relief for vulnerable consumers, ensuring openness in penalty communication, and implementing a phased payment scheme. Consequently, penalty policies can conform to national legislation while maintaining Islamic principles. This study aims to provide PT PLN with insights for formulating public service policies that are compassionate, accountable, and rooted in Islamic economic principles.